(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The aim of the research was to determine the growth and yield performance of some legumes upon exposure to heavy metals. seeds were collected from International Institute for Tropical Agriculture (IITA). Wild beans included TVNU2 and TVUN16, Cowpea: TVU2 and TVU8 while Bambara: TVSU3 and TVSU7. Dried soil collected was filled into 24 plastic buckets. Four (4) grams of lead chloride was measured with the aid of weighing balance and was dissolved into 1 litter of distilled water. Another portion of distilled water without any additive was measured and used as control. The lead solution was used to pollute the soil and allowed to stay for 24hrs before planting in a screen house. 4g of heavy metal was introduced into 8kg of soil in a bucket with each of the legumes having three replicates and was laid in a Randomized Complete Bock Design. The data collected was analyzed using two way (ANOVA) and treatment means were separated by means of LSD where differences exist. At 14 weeks after planting, results revealed that among the Cowpea accessions, TVU8 performed better than the other accession in all the parameters measured. Among the Wild bean, TVNU2 did better in most of the parameters except number leaf and number of pod/plant while in Bambara groundnut, TVSU7 performed best generally.